1982
DOI: 10.1111/j.1540-8159.1982.tb06560.x
|View full text |Cite
|
Sign up to set email alerts
|

The Underlying Heart Rhythm in Patients with an Artificial Cardiac Pacemaker

Abstract: One-hundred forty-two patients with atrioventricular block (AVB) and 61 patients with sick sinus syndrome (SSS) were followed for an average of 50 months after permanent pacemaker insertion. Their underlying heart rhythms (UHR) were evaluated repeatedly by chest wall stimulation (CWS). A deficient UHR was defined as ventricular asystole lasting 4 seconds or longer. The underlying conduction disturbance increased in 14% of AVB patients, decreased in 14%, and remained constant in 68%. The occurrence of Adams-Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
5
14
1
Order By: Relevance
“…In our study, PM dependency was found in 43.5% of the cases, similar to what has been reported in the human literature, where the time of onset is approximately 3 years …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, PM dependency was found in 43.5% of the cases, similar to what has been reported in the human literature, where the time of onset is approximately 3 years …”
Section: Discussionsupporting
confidence: 91%
“…In our study, most cases of 2:1 2AVB progressed to 3AVB in a variable period of time that ranged from 33 to 105 days. These results are not in agreement with findings in human patients where 2:1 2AVB is considered a stable AV conduction disturbance . These findings support the need for PMI in dogs with 2:1 2AVB, if other causes of AVB have been ruled out.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Permanent pacemaker recipients who have no intrinsic or escape rhythm may develop complications under conditions of electromagnetic interference, lead dysfunction, or battery depletion. Few studies have examined the incidence of pacemaker dependency after device implantation 1‐3 . A recent report from the Canadian Trial of Physiologic Pacing (CTOPP) Investigators indicated that pacemaker dependency, defined as an intrinsic heart rate ≤60 beats/min, has an important influence on cardiovascular and total mortality, as does the selection of pacing mode 1 .…”
Section: Introductionmentioning
confidence: 99%